Analisis Faktor Penurunan Gangguan Saluran Udara Tegangan Menengah (SUTM) Pada Penyulang Parangbanoa - Adriani Adriani (VERTEX ELEKTRO, 2021)
The reliability of the electric power system is one of the most important things to pay attention to in order to maintain the performance of the three main pillars of PT. PLN (Persero). The problem that often occurs in the distribution sector is interference with feeders. The purpose of this study was to determine the causes of trip feeder disturbances in parangbanoa feeders at PT. PLN (Persero) ULP Kalebajeng. The problem that often occurs in the distribution sector is feeder disturbance. Based on the results of the ArcGIS (Geometry Informindo System) output, the potential causes of trip disruption in the parangbanua feeders are trees and plants that affect SUTM, animals on the network, damaged JTM components, broken insulators, and less tight connections causing hot temperatures. Maintenance activities carried out are divided into integrated maintenance. saving obtained is 7,418 kWh / week, and the gain obtained can reach Rp. 10,882,206, - / week, while the benefits are a reduction in the number of interruption of feeder trips.